2,7-Dihydr-oxy-3,6-dimethoxy-phenanthrene from Dehaasia longipedicellata - Mukhtar, M.R.; Nafiah, M.A.; Awang, Khalijah; Hadi, A.H.A.; Ng, Seik Weng (International Union of Crystallography, 2008)
The hydr-oxy groups in the title compound, C(16)H(14)O(4), are each hydrogen bonded to the adjacent meth-oxy O atom; one of the two hydr-oxy groups is additionally linked to the O atom of the meth-oxy group of another mol-ecule, forming a linear chain.